2018
DOI: 10.1088/1361-6641/aae575
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of compressive strained Ge channels fabricated on Si (111) and Si (100)

Abstract: Structural properties of the strained Ge channels formed on SiGe (111) and SiGe (100) relaxed buffer layers are investigated. Compressive strained Ge(111) channels are grown on reverse graded Si 0.26 Ge 0.74 buffer layers, and as a result, very low rms roughness of 1.7 nm and large compressive strain of −0.92% are obtained. The phosphorous doping is attempted in the SiGe buffer for the purpose of suppression of parallel conduction and very abrupt doping is realized without very little diffusion. The high-quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…A Ge-on-Si(111) is useful templates since it has been shown that high quality Ge layers can be grown on Si (111) substrates by means of the two-step growth method. [24][25][26][27][28] Whilst such Ge-on-Si enables us to fabricate strained Si/Ge heterostructures on the Si platform, neither t c nor strain stability of the strained SiGe on Ge-on-Si in comparison with that on a Ge substrate has not been systematically explored.…”
mentioning
confidence: 99%
“…A Ge-on-Si(111) is useful templates since it has been shown that high quality Ge layers can be grown on Si (111) substrates by means of the two-step growth method. [24][25][26][27][28] Whilst such Ge-on-Si enables us to fabricate strained Si/Ge heterostructures on the Si platform, neither t c nor strain stability of the strained SiGe on Ge-on-Si in comparison with that on a Ge substrate has not been systematically explored.…”
mentioning
confidence: 99%
“…From the as-grown LM image shown in Fig. 1(b), it is found that line-shaped ridge roughness appears along three equivalent [1][2][3][4][5][6][7][8][9][10], and [01-1] directions though the relaxation ratio estimated from the XRD RSM measurement was almost 0 %. The distribution of the line-shaped ridge is seen to be quite non-uniform laterally.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the orientation of (111) is superior to (100) as the electron mobility of a Ge(111) channel is higher than that of a Ge(100) channel [4,5]. It has been experimentally shown that the interface roughness of the compressively strained Ge(111) channel layer grown on a relaxed SiGe was lower than that of the Ge(100) channel [6]. Moreover, Ge(111) and SiGe(111) with high Ge contents can be applied to spintronics devices because of the capability of lattice-matched epitaxial growth of high-quality ferromagnetic materials on them [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the surface of pure silicon with the (111) crystallographic orientation is traditionally used for germanium epitaxy [ 33 , 34 ] and is also very promising from the point of view of creating device structures [ 35 , 36 ], especially field-effect transistors [ 37 , 38 ] and photodiodes [ 39 ]. Some questions are devoted to Ge dewetting from Si(111) at high temperatures [ 40 ], strain relaxation [ 41 ], and formation of dislocations [ 42 , 43 ]. Moreover, Si(111) surface is used for epitaxy of GeSn [ 44 ] and SiGeSn [ 45 ] solid solution, as well as non-group-IV materials, for example, Au [ 46 , 47 ], Ga [ 48 ], GaN [ 49 , 50 ], GaSb [ 51 ] Bi 2 Te 3 [ 52 ], Se [ 53 ], etc.…”
Section: Introductionmentioning
confidence: 99%